The candidate antimalarial drug MMV665909 causes oxygen-dependent mRNA mistranslation and synergises with quinoline-derived antimalarials - Vallieres, Cindy; Avery, Simon V. (American Society for Microbiology, 2017)
To cope with growing resistance to current antimalarials, new drugs with novel modes of action are urgently needed. Molecules targeting protein synthesis appear to be promising candidates. We identified a compound (MMV665909) from the MMV Malaria Box of candidate antimalarials that could produce synergistic growth inhibition with the aminoglycoside antibiotic paromomycin, suggesting a possible action of the compound in mRNA mistranslation. This mechanism of action was substantiated with the yeast cell model using available reporters of mistranslation and other genetic tools. Mistranslation induced by MMV665909 was oxygen-dependent, suggesting a role for reactive oxygen species (ROS). Overexpression of Rli1 (a ROS-sensitive, conserved FeS protein essential in mRNA translation) rescued inhibition by MMV665909, consistent with the drug’s action on translation fidelity being mediated through Rli1. The MMV drug also synergised with major quinoline-derived antimalarials which can perturb amino acid availability or promote ROS stress: chloroquine, amodiaquine and primaquine. The data collectively suggest translation-fidelity as a novel target of antimalarial action and support MMV665909 as a promising drug candidate.